Can blended learning support improving english communication skills of the undergraduates in sri lanka? - Dharmawardene, R.P. (University of Jaffna, 2019)
Since the undergraduates enrolling in the one month English intensive course at the Faculty of Engineering in the University of Sri Jayewardenepura found it challenging to achieve the outcome of improving English writing skills, we explored whether two different delivery modes (face to face and blended) influenced their outcome achievement. Sixty students out of the 125 students who registered in the degree programme in 2018 consented to participate in the study. They were randomly assigned in to two groups. Two tutors of English taught the same content to the two groups of students using face-to-face and blended modes over one month. With the face to face mode utilized for the control group (n=30) and the blended mode for the experimental group (n=30), both groups received three learning modules and two writing assignments. The blended group received fifteen hour face to face learning sessions with six online lessons. They were also exposed to online chatting environment on LMS (URL=http://lms.tech.cmb.ac.lk/course/index. php?categoryid=8) to communicate with their peers and the teacher. Participants in the blended group were issued with a username and a password to access the LMS especially prepared for this study. The control group too received the same learning lesson materials but they practised those only in their face to face classes during thirty hour classroom sessions. The marks they scored at the pre and post tests were analyzed using paired t-tests in SPSS 20.0. At the pre test, both groups showed an equal level of performance in English writing. The same test was administered as the post test to the participants at the end of the intervention. The values of the post test marks at the significance level of p < .005 in the blended group (Mean= 54.67, t=-12.25, p=.000) comparing with that of the face to face group (Mean = 48.27, t=-7.58, p=.000) showed that the former was higher and more significant than the latter. The study showed that the English language writing skills of the engineering students in the blended group was significantly increased compared to that of the face to face group. Although the current study is based on a small sample of participants in one faculty of a university, the findings suggest that the blended learning approach can be successfully applied for undergraduates’ English learning.
Keywords: Online learning; Blended learning; English as a second language; Face-to-face learning; Higher education